Sediment transport and fluid mud layer formation in the macro-tidal Chikugo river estuary during a fortnightly tidal cycle. (5th March 2018) - Azhikodan, Gubash; Yokoyama, Katsuhide
Abstract: The erosion and deposition dynamics of fine sediment in a highly turbid estuarine channel were successfully surveyed during the period from August 29 to September 12, 2009 using an echo sounder in combination with a high-resolution acoustic Doppler current profiler. Field measurements were conducted focusing on the tide driven dynamics of suspended sediment concentration (SSC), and fluid mud at the upstream of the macrotidal Chikugo river estuary during semidiurnal and fortnightly tidal cycles. Morphological evolution was observed especially during the spring tide over a period of two weeks. The elevation of the channel bed was stable during neap tide, but it underwent fluctuations when the spring tide occurred owing to the increase in the velocity and shear stress. Two days of time lag were observed between the maximum SSC and peak tidal flow, which resulted in the asymmetry between neap-to-spring and spring-to-neap transitions. During the spring tide, a hysteresis loop was observed between shear stress and SSC, and its direction was different during flood and ebb tides. Although both fine sediments and flocs were dominant during flood tides, only fine sediments were noticed during ebb tides. Hence, the net elevation change in the bed was positive, and sedimentation took place during the semilunar tidal cycle. Finally, a bed of consolidated mud was deposited on the initial bed, and the height of the channel bed increased by 0.9 m during the two-week period. The observed hysteretic effect between shear stress and SSC during the spring tides, and the asymmetrical neap-spring-neap tidal cycle influenced the near-bed sediment dynamics of the channel, and led to the formation of a fluid mud layer at the bottom of the river. Highlights: Interaction between fluid mud, fine sediments and flocs in the ETM zone. Erodibility was higher for deposited mud during flood tide than that during ebb tide. Fluid mud layer formed within a span of two weeks in a turbid estuarine channel. Hysteresis effect between shear stress and SSC during spring tides. Fluid mud dynamics is an asymmetrical neap-spring-neap tidal influenced phenomenon.